The Microvascular Carpal Foot Pad Flap: Vascular Anatomy and Surgical Technique - Moens, N. M. M.; Fowler, J. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The objectives of the study are to describe the vascular anatomy of the carpal foot pad and to describe the surgical technique for its dissection as a free microvascular flap.Sixteen front legs from ten different dogs weighing from 20 to 30 kg were used for the study. All of the dogs were euthanatized for reason unrelated to the study. Dissection of the carpal foot pad with its dominant arterial and venous pedicle was performed and angiographic studies were performed by injection of barium sulphate and “high detailed” radiography.The vascular anatomy of the carpal foot pad was consistent in all of the dogs. The arterial pedicle arises from the caudal interosseous artery and venous drainage is provided by the cephalic vein. A branch of the ulnar nerve parallels the arterial blood supply and may be included in flap dissection. Surgical dissection of the carpal foot pad flap is relatively straight forward. The length and diameter of the arterial and venous pedicle are appropriate for microvascular anastomosis.The carpal foot pad in the dog represents a viable option for microvascular transfer and reconstruction of weight bearing surfaces.Cadaveric dissection was used to study the vascular anatomy of the carpal foot pad in dogs and to assess its potential use as a free microvascular flap.
Keywords: Foot pad; microvascular; reconstruction; dog